Pengaruh Model Pembelajaran STAD terhadap Kemampuan Berpikir Kritis Siswa Multietnis di SMP Negeri Kota Ternate - Ermin Ermin; Najamudin Marsaoly (Peneliti.net, 2021)
Critical thinking is an effective and reasonable thinking process that focuses on beliefs and actions that are carried out reliably. Critical thinking skills have an important role in improving human quality. However, critical thinking skills in schools have not been empowered properly. Until now, conventional learning is still a common model in learning because it is considered to be an option to be applied to an application of learning that requires a relatively short time, the scope of the material taught is wider and can equip students with conceptual understanding. The learning approach that must be taken by the teacher in improving students' critical thinking skills is to use cooperative learning. The model that is expected to empower students' critical thinking is STAD type cooperative learning. This research is a quasi-experimental research (quasi-experimental). Experimental research aims to determine the effect of the STAD learning model on the critical thinking skills of multiethnic junior high school students in Ternate City. The design used in this research is the Pretest-Posttest Nonequivalent Control Group Design. The number of samples was 38 students consisting of students from SMP Negeri 2 which opened 18 people and SMP Negeri 3 which found 20 people. The entire sample of students consisted of ethnic Ternate 13, Makian 12 and Tidore 13 students. The STAD learning model has a significant effect on the critical thinking ability of multiethnic students in Ternate City Junior High School, ethnicity has a significant effect on the critical thinking ability of multiethnic students in Ternate City Junior High School and the interaction of learning and ethnic models significantly affects students' critical thinking skills. Further test results showed that the STAD learning model might improve the critical thinking skills of Ternate, Makian and Tidore ethnic students.